Modeling and experimental validation of two adjacent portal frame structures subjected to vibro-impact - Varanis, Marcus V. M. [UNESP]; Mereles, Arthur G.; Silva, Anderson L.; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; Oliveira, Clivaldo (FapUNIFESP (SciELO), 2019)
In many engineering applications, there are systems that exhibit a series of collisions in a certain amount of time, for example the impact of floating ice in ships and the rubbing between stationary and rotary parts in turbomachinery. In many of these situations, it is of vital importance to know how the impacts affect the overall system behavior for the correct functioning or the prediction of faults in the system. This can be done by proposing models that can represent the system when it is subjected to sudden impacts in its oscillation movement. However, due to the nonlinear and non-smooth characteristic of the impact phenomenon, the implementation of impacts in mechanical systems may be a challenging task. In this manner, this paper aims in proposing a vibro-impact model of two adjacent portal frame structures, being one of them driven by an unbalanced DC motor positioned on top of it. The portal frames were modeled as continuous beams by means of the Euler-Bernoulli beam theory. In order to model the impact between the structures, three different models were considered: using the Hertz theory of elastic bodies to model the contact force using a nonlinear damping; using a spring and a damper in parallel, viscoelastic or spring-dashpot system, to model the force; and considering the impact to be instantaneous and using the coefficient of restitution to adjust the velocity after the contact. To validate the impact models, an experimental procedure was performed and the measurements compared with the simulations.
Keywords: Euler-Bernoulli theory; Experimental validation; Nonlinear model; Numeric simulations; Vibro-impact